Analisis Kesesuaian Materi Dalam Buku Siswa Bahasa Indonesia Kelas VII Edisi Revisi 2017 Terbitan Kemendikbud Dengan KI Dan KD Pada Kurikulum 2013 - Yohana Br Manalu (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
The existence of textbooks cannot be separated from the curriculum that is implemented. In reality, the textbooks in circulation are still not in accordance with the content standards contained in the curriculum. This research aims to find out and describe the material contained in the 2017 Revised Edition of the Indonesian Language Student Book for Class VII published by the Ministry of Education and Culture with KI and KD in the 2013 Curriculum. To achieve the above objectives, qualitative research methods were used. The data and data source for this research is the 2017 Revised Edition of the Indonesian Language Student Book for class VII. The type of instrument used in this research uses a checklist. The data collection technique in this research is the reading technique, the word technique. In this research, the data analysis technique uses content analysis. Based on the results of the analysis of the suitability of the material in the 2017 Revised Edition of the Indonesian Language Student Book for Class VII with the KI and KD in the Curriculum, if the results are as a percentage, namely 50% of the discrepancy lies in the order of the textbook material to the KI and KD. This means that the sequence of material in the second semester does not match the sequence in the curriculum.